Pendampingan Komunikasi Bahasa Inggris bagi Pelaku Wisata Negeri Saleman melalui Pendekatan English for Specific Purposes (ESP) - Henry Latuheru; Ayu Aprilya Sari Abdullah (Civiliza Publishing, 2026)
Negeri Saleman, North Seram District, Central Maluku Regency, is one of the leading marine tourism destinations in Maluku Province, often referred to as 'Indonesia's Maldives'. The growing influx of international tourists to this area, including Belarisky Resort, presents a challenge in the form of limited English communication skills among staff. This community service program (PKM) aims to improve the English competence of Belarisky Resort staff through an English for Hospitality training program based on the English for Specific Purposes (ESP) approach. The methods employed include needs analysis, module development, interactive training using simulation and role-play techniques, and pre-test/post-test evaluation. The results indicate a significant improvement in participants' hospitality vocabulary and conversational skills, positively impacting their confidence and service quality toward international guests. This program is expected to serve as an ESP-based language training model for other tourism destinations in Maluku and Eastern Indonesia.